Urgensi Pengaturan Hukum dan Tanggung Jawab terhadap Praktik Bedah Robotik dalam Perspektif Hukum Pidana di Indonesia - Aprilia Nurazizah; Heriamariaty Heriamariaty; Putri Fransiska Purnama Pratiwi; Agus Mulyawan (Jurnal Hukum Lex Generalis, 2026)
Advances in healthcare technology have given rise to robotic surgery, which increases the precision of medical procedures. This study aims to analyze the legal gaps in the regulation and accountability of robotic surgical practices in Indonesia and compare them with regulations in the United States. The method used is normative juridical, with legislative, conceptual and comparative approaches. The results indicate a lack of specific regulations regarding the classification of robotic surgical devices and liability for system malfunctions. The United States, through the FDA, has implemented clear classification and oversight standards. This study recommends the establishment of specific regulations, operator certification standards and clear accountability mechanisms in robotic surgical practices.